Strategi peningkatan kapasitas usaha pengolahan sukun pada BUMDes Temmappettue Teamalala Kabupaten Bone - Ramadhan, Ramadhan; Rahman, Syamsul; Ibrahim, Helda (Journal of Agribusiness Science and Rural Development, 2025)
Breadfruit (Artocarpus altilis) from Bone has long been recognized, particularly in South Sulawesi, and the region is one of the main national production centers. Efforts to enhance the added value of breadfruit are carried out through small and medium enterprises (SMEs) engaged in processing activities. The Village-Owned Enterprise (BUMDes) Temmappettue in Ulaweng Subdistrict represents one of the local initiatives focusing on processing breadfruit into derivative products such as chips and flour. This study aims to analyze capacity-strengthening strategies for breadfruit-based SMEs managed by BUMDes Temmappettue by identifying internal and external factors and formulating appropriate strategic priorities. The research employs a descriptive qualitative method, with data collected through in-depth interviews, observation, documentation, and literature review. Data analysis was conducted using a SWOT approach, followed by the construction of IFAS and EFAS matrices to determine the enterprise’s strategic position. The findings reveal that the main strengths lie in the strong reputation of Bone breadfruit and the possession of business legality and product certifications, while the major weaknesses include limited skilled human resources and suboptimal use of digital marketing. Opportunities that can be leveraged include training and mentoring support from stakeholders and partnerships with culinary businesses, whereas the primary threats are the company’s limited adaptability to dynamic marketing trends and the seasonal nature of breadfruit as raw material. The SWOT mapping places the enterprise in Quadrant I (aggressive strategy), indicating that development strategies should focus on product diversification, human resource capacity building, optimization of digital marketing, and brand strengthening through product certification and business legality. The study concludes that strengthening breadfruit-based SMEs under BUMDes Temmappettue in Bone Regency has the potential to enhance competitiveness, expand market access, and contribute to local food security and rural community welfare.